OPTIMIZING HOSPITAL SERVICE MANAGEMENT IN THE ERA OF HEALTH TRANSFORMATION - Nasikin, Moch (Medical Journal of Nusantara, 2025)
This study aims to analyze the effectiveness, efficiency, and quality of hospital services in a sustainable manner within the era of healthcare transformation. The research employed a mixed methods approach with a sequential explanatory design, combining quantitative analysis of hospital performance indicators with qualitative exploration of service management practices. Effectiveness indicators included Bed Occupancy Ratio (BOR), Length of Stay (LOS), and Turn Over Interval (TOI); efficiency was measured through Bed Turn Over (BTO), Cost Recovery Rate (CRR), and waiting time; while service quality was assessed using patient satisfaction index and patient safety indicators. The findings indicate that data-driven management strengthening, digitalization of hospital information systems, and the implementation of continuous quality improvement significantly contribute to improving hospital service performance. The integration of clinical effectiveness, operational efficiency, and service quality forms the foundation for hospital sustainability in responding to regulatory demands and national healthcare transformation initiatives.